Fungsi Penggunaan Merek Untuk Produk Usaha Rumahan (Abon Ikan) Bagi Desa Tambu - Mehdi Mohammad Fahrullah Al-hasni; Muhammad Din; Maskuri Sutomo (Jurnal Nusantara Berbakti, 2023)
The purpose of this community service activity is to provide information and knowledge related to the importance of brands to the community in Tambu Village, Balaesang District, Donggala Regency as a form of learning for home-based businesses. The MBKM student activity method used is in the form of education or providing information on brand functions. The use of the mark on shredded fish product packaging to provide a mark on the product, as a means of promotion, shows the quality of the product and the origin of the product. Providing learning about the function of the brand given by the MBKM Faculty of Economics students to the people of Tambu Village as an effort to provide education on the importance of using a brand. In addition, using a brand serves to provide an identity for goods or services and functions to ensure quality and combination for consumers.